Restriction endonuclease cleavage map of the DNA of JC virus. - Martin, J D (1979)
A physical map of the sites cleaved by the following restriction endonucleases was derived for the DNA of JC virus, a human polyomavirus: EcoRI, HpaI, and PstI (one site each); HindII (four sites); and HindIII (three sites). By agarose gel electrophoresis of fragmented DNA, the size of full-length DNA of JC virus was estimated to be 5,125 +/- 105 base pairs (98 +/- 2% of the length of simian virus 40 DNA).